تقويم كتابي الفيزياء للمرحلة الإعدادية في ضوء المستحدثات العلمية المعاصرة (Journal Of Educational and Psychological Researches, 2016)
The present study aimed to measure the calendar estimates for my book Physics of the preparatory phase (fourth and fifth preparatory) has been a research sample consisted of 32 teachers and a school for 36 schools from both sides of the Rusafa and Karkh first To achieve the objectives Find promised researcher tool for measuring the calendar estimates for my book Physics of the preparatory phase in accordance with the contemporary scientific innovations as formed tool from 5 innovations built on the basis of which the paragraphs which formed the final version of the 21 paragraph manual are not substitutes to answer yes -No Your has been used Baha percentages to reach the results may reach current research conclusion which is deficiencies in the vocabulary of the curriculum and dealing with the most important contemporary scientific innovations that are very important in the life of the individual and the environment